Segmental Duplication of Chromosome 11 and its Implications for Cell Division and Genome-wide Expression in Rice - Rong Zhang (Nature Portfolio, 2017)
Abstract Segmental duplication is a major structural variation that occurs in chromosomes. Duplication leads to the production of gene copies with increased numbers of related repeat segments, causing the global genome to be in a state of imbalance. In addition, if the added segment contains a centromeric specific DNA, the duplicated chromosome will have structural multiple centromeres. We identified a segmental duplication containing structurally tricentric regions derived from the short arm of chromosome 11 (11L∙ + 11L∙ + 11S∙11S∙11S∙11S, “∙” represents the centromeric DNA repeat loci), and analyzed its implications for cell division and genome-wide expression. In the variant, only the middle centromere of 11S∙11S∙11S∙11S is functionally active. As a result, the structurally tricentric chromosome was stable in mitosis, because it is actually a functional monocentric chromosome. However, the structurally tricentric chromosome, which usually formed a bivalent, was either arranged on the equatorial plane or was lagging, which affected its separation during meiosis. Furthermore, RNA-seq and RT-qPCR analysis showed that the segmental duplication affected genome-wide expression patterns. 34.60% of genes in repeat region showed positive dosage effect. Thus, the genes on chromosome arm 11S-2 didn’t exhibit obviously dosage compensation, as illustrated by no peak around a ratio of 1.00. However, the gene dosage effect will reduce after sexual reproduction of a generation.